Analisis Resepsi Cinta Buta dalam Film Horor Do You See What I See “First Love” - Ryandhika Rezky Setiawan; Aryo Subarkah Eddyono (CV. ITTC INDONESIA, 2026)
Adapting a horror podcast into a feature film raises issues related to differences in audience interpretation of media messages, particularly in the representation of the theme of blind love shown in horror films. The differences in characteristics between audio and visuals have the potential to produce diverse interpretations, so audience interpretation requires further study. This study aims to analyze audience interpretation of the representation of blind love in the film Do You See What I See: “First Love” (2024), adapted from a horror podcast of the same title. The focus of the research is directed at the audience's position in the message decoding process based on media communication theory. This study uses a qualitative approach with Stuart Hall's reception analysis method through the encoding-decoding framework. Data were obtained through in-depth interviews with three informants who are both podcast listeners and film viewers, supported by participant observation and documentation. Data analysis techniques used thematic analysis to group audience interpretations into dominant-hegemonic, negotiated, and oppositional categories, and strengthened by triangulation of sources and techniques. The results show that audiences interpret blind love as a form of emotional attachment that blocks rationality and has the potential to cause negative impacts. One informant held a dominant-hegemonic position, accepting the film's moral message in its entirety, while two informants held a negotiated position, negotiating meaning based on their aesthetic experience, professional background, and preference for the horror genre. These findings indicate that audiences actively interpret media messages and that meaning is not accepted in isolation but rather is shaped through a process of negotiation based on the audience's social background and experiences.